Liver gene transfection by retrograde intrabiliary infusion facilitated by temporary biliary obstruction. (9th January 2020) - Dai, Chenguang; Wang, Min; Zhao, Lili; Xu, Chunfang; Huang, Jin; Fan, Zhining
Abstract: Background: The hepatobiliary tract may be a valuable administration site for gene delivery. We demonstrated the role of temporary biliary obstruction for gene transfection by retrograde intrabiliary infusion. Methods: Male Sprague–Dawley rats received intrabiliary infusion of luciferase plasmid via an artificial common bile duct, with temporary biliary obstruction for 0 minutes (NO group), 30 minutes (30 min group) and 24 hours (24 h group), respectively ( n = 4 for each group). Gene expression levels were evaluated by luciferase bioluminescence on postoperative days (POD) 1, 2 and 7. Serum and livers were collected on POD 1 and 14 for liver biochemistry, hematoxylin and eosin staining, and immunohistochemistry. Results: On POD 1, luciferase chemoluminescence was significantly higher in the 24 h group than in the NO group ( p = 0.002) and the 30 min group ( p = 0.002). However, it decreased rapidly after reversal of the obstruction in the 24 h group (POD 1 versus POD 2, p = 0.002; POD 1 versus POD 7, p = 0.002). Liver biochemistry was changed on POD 1, but no significant differences were detected after 14 days of recovery ( p > 0.05). Similar histological changes were found in the three groups, with no unwanted proliferation of biliary epithelial cells. The obstruction did not cause serious liver damage. Conclusions: Temporary biliary obstruction for 24 hours facilitated the safe, feasible and effective transfection of plasmid DNA into the liver via the hepatobiliary tract. In the future, endoscopic retrograde cholangiopancreatography and its dilation balloon could be used to create biliary obstruction and allow the direct gene delivery into the liver. More research is necessary for achieving stable gene expression, as well as in terms of weighing its benefits against potential complications.